Ultrasound-assisted extraction optimization of polyphenols from Boletus bicolor and evaluation of its antioxidant activity - Hu, Dong-Bao; Xue, Rui; Zhuang, Xiao-Cui; Zhang, Xin-Sha; Shi, Sheng-Li (Frontiers in Nutrition, 2023)
Introduction Boletus bicolor (B. bicolor) mushrooms are widely consumed as a valuable medicinal and dietary ingredient in China, but the active ingredients of this mushroom and their extraction methods were not extensively studied. Methods In this paper, we propose an optimized ultrasound-assisted extraction (UAE) method to detect natural antioxidant substances in B. bicolor. The antioxidants were quantitatively and quantitatively determined using UPLC-MS, the polyphenols were evaluated based on response surface methodology (RSM), and density functional theory (DFT) calculations were performed. Results The results showed that the optimal extraction was obtained under the following conditions: ethanol concentration 42%; solvent to solid ratio 34:1 mL/g; ultrasonic time 41 min; and temperature 40°C. The optimized experimental polyphenol value obtained under these conditions was (13.69 ± 0.13) mg/g, consistent with the predicted value of 13.72 mg/g. Eight phenolic compounds in the extract were identiffed by UPLC-MS: syringic acid, chlorogenic acid, gallic acid, rosmarinic acid, protocatechuic acid, catechin, caffeic acid, and quercetin. Chlorogenic acid exhibits the highest HOMO energy (−0.02744 eV) and the lowest energy difference (−0.23450 eV) among the studied compounds, suggesting that the compound might be the strongest antioxidant molecule. Eight phenolic compounds from the B. bicolor signiffcantly inhibited intracellular reactive oxygen species (ROS) generation, reduced oxidative stress damage in H2O2-induced HepG-2 cells. Discussion Therefore, it was confirmed that the UAE technique is an efficient, rapid, and simple approach for extracting polyphenols with antioxidant activity from B. bicolor.